Untargeted Metabolomics Investigation on Selenite Reduction to Elemental Selenium by Bacillus mycoides SeITE01 - Baggio, Greta; Groves, Ryan A.; Chignola, Roberto; Piacenza, Elena; Presentato, Alessandro; Lewis, Ian A.; Lampis, Silvia; Vallini, Giovanni; Turner, Raymond J. (Frontiers in Microbiology, 2021)
Bacillus mycoides SeITE01 is an environmental isolate that transforms the oxyanion selenite (SeO32-) into the less bioavailable elemental selenium (Se0) forming biogenic selenium nanoparticles (Bio-SeNPs). In the present study, the reduction of sodium selenite (Na2SeO3) by SeITE01 strain and the effect of SeO32- exposure on the bacterial cells were examined through untargeted metabolomics. A time-course approach was used to monitor both cell pellet and cell free spent medium (referred as intracellular and extracellular, respectively) metabolites in SeITE01 cells treated or not with SeO32-. The results show substantial biochemical changes in SeITE01 cells when exposed to SeO32-. The initial uptake of SeO32- by SeITE01 cells (3-h time after inoculation) shows both an increase in intracellular levels of 4-hydroxybenzoate and indole-3-acetic acid, and an extracellular accumulation of guanosine, which are metabolites involved in general stress response adapting strategies. Proactive and defensive mechanisms against SeO32- are observed between the end of lag (12-h) and beginning of exponential (18-h) phases. Glutathione and N-acetyl-L-cysteine are thiol compounds that would be mainly involved in Painter-type reaction for the reduction and detoxification of SeO32- to Se0. In these growth stages, thiol metabolites perform a dual role, both acting against the toxic and harmful presence of the oxyanion and as substrate or reducing sources to scavenge ROS production. Moreover, detection of the amino acids L-threonine and ornithine suggest changes in membrane lipids. Starting from stationary phase (24 and 48-h), metabolites related to the formation and release of SeNPs in the extracellular environment begin to be observed. 5-hydroxyindole acetate, D-[+]-glucosamine, 4-methyl-2-oxo pentanoic acid, and ethanolamine phosphate may represent signaling strategies following SeNPs release from the cytoplasmic compartment, with consequent damage to SeITE01 cell membranes. This is also accompanied by intracellular accumulation of trans-4-hydroxyproline and L-proline, which likely represent osmoprotectant activity. The identification of these metabolites suggests the activation of signaling strategies that would protect the bacterial cells from SeO32- toxicity while it is converting into SeNPs.